Technological innovation in a case of protected agriculture in Mexico - Vargas Canales, Juan Manuel (2018)
The objective of this research was to analyze technological change and innovation, how technology is transmitted and the networks linked to protected agriculture from a territorial approach in the state of Hidalgo, Mexico. Technological trajectory, the genealogical method and sociotechnical networks were used for its analysis. Results indicate that the trajectory occurred through the accumulation of technological changes, driven by development policies. Genealogies show that technology is introduced, adapted and reproduced by innovative agents who maintain relationships with universities and public institutions. Sociotechnical networks are characterized by their breadth, heterogeneity and clear articulation among actors; the extensionists are responsible for mediation and harmonization of processes and the creation of links and relationships among actors. Regional specialization was the key to the development of protected agriculture; however, it is necessary to diversify products, explore new markets and manage organization. Finally, the analytical approach used makes it possible to understand technological change and innovation in agricultural production systems.